The Interaction Between Pictures and their Labels in the Memory of Four-Year-Old Children - Wilgosh, Lorraine Rose (My University, 1970)
The reported experiments were concerned with the role of pictures and words in the memory of four-year-old children. The experiments demonstrated that providing four-year-old children with verbal labels facilitated their visual recognition and free verbal recall of pictures. This was true not only of labels, but also of longer, less-rehearsible descriptive phrases which did not necessarily suggest corresponding names. Furthermore, this finding was obtained when the labels, by themselves, did not permit the subject to distinguish between the alternatives on the visual recognition test. These findings indicate the inadequacy of a strictly response-oriented explanation of the results; neither rehearsal of the specific words by themselves nor their production at the retention test are sufficient to explain the recognition results. Instead, the effect of words was apparently to influence the subjects to process or store the information in the pictures differently than they would have done in the absence of the words.
Keywords: interaction, pictures, labels, memory, children